2019
DOI: 10.3390/ijerph16183240
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in the HIV Testing during Antenatal Care in Vietnamese Women

Abstract: Although HIV (human immunodeficiency virus) testing for all women has been promoted by Vietnam’s Ministry of Health since 2000, test acceptance rates in this country were reported to be less than 30% in the community. This country has been facing the barriers to approach the national services towards transmission prevention from mother to child including HIV testing during antenatal care (ANC) towards mothers. Here, we aim to assess the socioeconomic inequalities in HIV testing during ANC among Vietnamese wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
4
23
0
Order By: Relevance
“…This study showed the existence of socioeconomic inequality in prenatal HIV test service utilization in East Africa with this being 15.94% higher among the rich than the poor (p<0.001). This result is consistent with most studies in developing countries, in which women with higher SES had a high probability of using a range of maternal health services including HIV test services during pregnancy [ 31 , 54 56 ]. However, the finding contradicts a study in South Africa [ 39 ] that found pro-poor inequality of HIV testing during pregnancy among women attending public health facilities.…”
Section: Discussionsupporting
confidence: 91%
“…This study showed the existence of socioeconomic inequality in prenatal HIV test service utilization in East Africa with this being 15.94% higher among the rich than the poor (p<0.001). This result is consistent with most studies in developing countries, in which women with higher SES had a high probability of using a range of maternal health services including HIV test services during pregnancy [ 31 , 54 56 ]. However, the finding contradicts a study in South Africa [ 39 ] that found pro-poor inequality of HIV testing during pregnancy among women attending public health facilities.…”
Section: Discussionsupporting
confidence: 91%
“…However, a recent study showed that 25% of people receiving ART reported nonoptimal adherence and missed 25% of doses in the last 7 days. 11 HIV/AIDS prevention and control in Vietnam is facing several challenges with inequalities in receiving health services 12,13 ; thus, more endeavours are needed in progress towards HIV elimination in this low-and middle-income country. 14 Since HAART non-adherence is one of the most serious challenges to the success of HIV treatment, much has been done to identify its associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…analysed data of 1,484 women aged 15–49 with live births in the last two years and received HIV testing during antenatal care reported that 88.9% of pregnant women was 34 years old or younger and 83% were Kinh ethnics. 43 In our study, 91.1% pregnant women were 34 years-old or younger and although our study did not collect information on ethnics, 84% people lived in Pho Yen district were Kinh ethnics.…”
Section: Discussionmentioning
confidence: 71%